Ligamentum teres augmentation (LTA) for hiatal hernia repair after minimally invasive esophageal resection: a new use for an old structure - Runkel, Mira; Kuvendjiska, Jasmina; Marjanovic, Goran; Fichtner-Feigl, Stefan; Diener, Markus K. (Langenbeck's archives of surgery, 2021)
Hiatal hernias with intrathoracic migration of the intestines are serious complications after minimally invasive esophageal resection with gastric sleeve conduit. High recurrence rates have been reported for standard suture hiatoplasties. Additional mesh reinforcement is not generally recommended due to the serious risk of endangering the gastric sleeve. We propose a safe, simple, and effective method to close the hiatal defect with the ligamentum teres.
Gesehen am 18.08.2023